2014
DOI: 10.1523/jneurosci.5025-12.2014
|View full text |Cite
|
Sign up to set email alerts
|

Extended Wakefulness: Compromised Metabolics in and Degeneration of Locus Ceruleus Neurons

Abstract: Modern society enables a shortening of sleep times, yet long-term consequences of extended wakefulness on the brain are largely unknown. Essential for optimal alertness, locus ceruleus neurons (LCns) are metabolically active neurons that fire at increased rates across sustained wakefulness. We hypothesized that wakefulness is a metabolic stressor to LCns and that, with extended wakefulness, adaptive mitochondrial metabolic responses fail and injury ensues. The nicotinamide adenine dinucleotide-dependent deacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
138
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 58 publications
2
138
1
Order By: Relevance
“…37 Avoidance of severe hypoxia during REM, by contrast, appeared to protect against neuronal degeneration in the locus ceruleus, an area involved in alertness and control of sleep architecture. In animal studies, hypoxia 38 and extended wakefulness 39 lead to neuronal degeneration in the locus ceruleus, and damage to this area is seen in Parkinson disease and REM sleep behavior disorder. 40 It remains unclear to what extent neuronal changes in this area may either lead to or result from changes in sleep architecture and SDB.…”
Section: Methods Study Population the Honolulu-asia Agingmentioning
confidence: 99%
“…37 Avoidance of severe hypoxia during REM, by contrast, appeared to protect against neuronal degeneration in the locus ceruleus, an area involved in alertness and control of sleep architecture. In animal studies, hypoxia 38 and extended wakefulness 39 lead to neuronal degeneration in the locus ceruleus, and damage to this area is seen in Parkinson disease and REM sleep behavior disorder. 40 It remains unclear to what extent neuronal changes in this area may either lead to or result from changes in sleep architecture and SDB.…”
Section: Methods Study Population the Honolulu-asia Agingmentioning
confidence: 99%
“…A recent animal study showed that sleep deprivation can result in neuronal loss in the locus coeruleus [76], which may lead to negative cognitive consequences. This is a candidate mechanism explaining how self-reported short sleep might lead to poorer cognitive function in older adults.…”
Section: Overlapping Neural Correlates For Decreasing Sleep and Perfomentioning
confidence: 99%
“…Sleep deprivation itself has been shown to be negatively correlated with memory function, as well as, in the context of international testing of academic achievement (Diekelmann & Born, 2010;Mullis et al, 2012). The social and cultural changes incurred by technology-associated chrono-disruption should not be overlooked (Ekirch, 2001;Kantermann 2013) and should be an increasing concern with the contribution of technology, and the educational use of technology on disruption of optimal sleep patterns (West et al, 2011) and the effects of this on brain function (Yuan et al, 2011;Yang et al, 2014;Zhang et al, 2014), which undoubtedly impact on academic achievement.…”
Section: Discussionmentioning
confidence: 99%